Pengukuruan Produktivitas Dengan Menggunakan Metode Objective Matrix di PT.ABC - Muhamad Bob Anthony (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2019)
PT. ABC is a chemical company that produces emulsions. Evaluation of performance development in the production department requires a measurement of productivity with the aim of knowing the level of productivity in the production section that has been achieved based on the criteria that are indicators of productivity in the form of ratios, identifying the causes of the decline in productivity and making improvement plans in an effort to continuously increase productivity. The method used in measuring productivity in this study is the Objective Matrix method so the steps in this study refer to the need for matrix formation. Based on the measurement of the productivity value in the production section before making improvements with the Objective Matrix method for the 6 months period July 2017 to December 2017 the lowest productivity value was obtained in December 2017. The factor that caused this lowest productivity value was the very long reactor washing for 24 hours. Washing the reactor is very long because the washing method is still done manually. The productivity value increased after there was an improvement by shortening the reactor cleaning time by using the 300 bar pressurized water jet cleaner method, namely in January 2019 to 738 or 560.76% compared to the previous period and an increase of 146.0% compared to the standard productivity value. PT.ABC merupakan salah satu perusahaan kimia yang memproduksi emulsi. Evaluasi perkembangan kinerja di bagian produksi memerlukan suatu pengukuran produktivitas dengan tujuan mengetahui tingkat produktivitas di bagian produksi yang telah dicapai berdasarkan kriteria-kriteria yang menjadi indikator produktivitas dalam bentuk rasio, mengidentifikasi penyebab terjadinya penurunan produktivitas dan melakukan perencanaan perbaikan sebagai upaya peningkatan produktivitas secara berkesinambungan. Metode yang digunakan dalam pengukuran produktivitas dalam penelitian ini adalah metode Objective Matrix sehingga langkah-langkah pada penelitian ini mengacu pada kebutuhan pembentukan matrik. Berdasarkan pengukuran nilai produktivitas di bagian produksi sebelum dilakukan perbaikan dengan metode Objective Matrix selama 6 bulan periode Juli 2017 sampai Desember 2017 diperoleh nilai produktivitas terendah di bulan Desember 2017. Faktor yang menyebabkan nilai produktivitas terendah ini adalah pencucian reaktor yang sangat lama yaitu selama 24 jam. Pencucian reaktor ini sangat lama dikarenakan metode pencucian masih dilakukan secara manual. Nilai produktivitas mengalami peningkatan setelah ada perbaikan dengan mempersingkat waktu pencucian reaktor dengan menggunakan metode water jet cleaner bertekanan 300 bar yaitu pada Januari 2019 menjadi 738 atau 560.76% dibandingkan periode sebelumnya dan mengalami peningkatan 146.0% dibandingkan nilai produktivitas standar.